2022
DOI: 10.3390/jcm11092294
|View full text |Cite
|
Sign up to set email alerts
|

Myopia Control Effect Is Influenced by Baseline Relative Peripheral Refraction in Children Wearing Defocus Incorporated Multiple Segments (DIMS) Spectacle Lenses

Abstract: The aim of this study is to investigate if baseline relative peripheral refraction (RPR) influences the myopia control effects in Chinese myopic children wearing Defocus Incorporated Multiple Segments (DIMS) lenses. Peripheral refraction at 10°, 20°, and 30° nasal (10 N, 20 N, 30 N) and temporal (10 T, 20 T, 30 T) retina were measured at six-month intervals for children who participated in a 2-year randomized controlled trial. The relationship between the baseline peripheral refractions and myopia progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…These preliminary results were confirmed after a 3-year follow-up, showing that the myopia control effect was sustained in the third year in children who had used the DIMS spectacles in the previous 2 years and was also shown in the children switching from single vision to DIMS lenses [ 142 ]. Interestingly, in a study by Zhang et al, [ 143 ] baseline relative peripheral refraction (RPR) was assessed as a variable on the myopia control effects in myopic children wearing DIMS lenses. The authors concluded that DIMS lenses slowed down myopia progression, and myopia control was better for the children with baseline hyperopic RPR than the children with myopic RPR.…”
Section: Optical Strategiesmentioning
confidence: 99%
“…These preliminary results were confirmed after a 3-year follow-up, showing that the myopia control effect was sustained in the third year in children who had used the DIMS spectacles in the previous 2 years and was also shown in the children switching from single vision to DIMS lenses [ 142 ]. Interestingly, in a study by Zhang et al, [ 143 ] baseline relative peripheral refraction (RPR) was assessed as a variable on the myopia control effects in myopic children wearing DIMS lenses. The authors concluded that DIMS lenses slowed down myopia progression, and myopia control was better for the children with baseline hyperopic RPR than the children with myopic RPR.…”
Section: Optical Strategiesmentioning
confidence: 99%
“…In the 42 to 72 months, the myopic progression in the 8-year-old group was still faster than in other age groups. We have discussed this observation in two publications 37 , 38 that relative peripheral refraction (RPR) at the start of the treatment has some impact on myopia control outcomes. Most children with younger enrolment age (aged 8 years) in the 2-year RCT of DIMS lenses had myopic RPR at baseline 37 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…We have discussed this observation in two publications 37 , 38 that relative peripheral refraction (RPR) at the start of the treatment has some impact on myopia control outcomes. Most children with younger enrolment age (aged 8 years) in the 2-year RCT of DIMS lenses had myopic RPR at baseline 37 , 38 . They showed less myopia control effects compared with the other age groups who had baseline hyperopic RPR and this impact continues to older age despite continuation with treatment lenses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations